Bimbingan Teknis Pengelolaan Website Fakultas dan Program Studi di Lingkungan Universitas Almuslim Bireuen - Aceh - Marwan, Marwan; Win, Konadi; Riyadhul, Fajri; Husni, Abda (Aceh Journal of Community Engagement (AJCE), 2023)
Lecturer service activities in the form of technical guidance (Bintek) aim to increase participants' understanding and ability to manage websites properly and correctly, quickly and effectively in the context of public services related to programs and education within Almuslim University (Umuslim). The implementation of activities in the Umuslim Postgraduate IT workroom on August 3 2023 involved 8 (eight) website managers representing the university level, faculties/study programs and institutions/agencies within Umuslim with an emphasis on material and practices for managing healthy, correct and effective website content. The results of the activity show an increase in ability and understanding of the application of managing WordPress-based website content. So it is hoped that the existence of a website in each work unit will be able to provide services to the community and stakeholders in the future.